Microstructure Characterization of Degraded Grease in Axle Roller Bearings. Issue 4 (4th July 2019) - Lin, Chih-Ling; Meehan, Paul A.
Abstract: Aged mineral-oil-based, lithium-hydroxystearate-thickened grease was collected from used axle spherical roller bearings, which were used for urban commuter trains. Three types of aged grease were categorized based on the total distance that the bearing had traveled, as early life (<0.05 million km [M.km]), medium (0.3–0.6 M.km), and heavily used (1.82 and 2.0 M.km). The microstructure of degraded grease from 20 bearings was characterized in this project using atomic force microscopy (AFM) and scanning electron microscopy (SEM). Base oil of each grease sample was released by a centrifugation method and the oxidation of bled oil was measured by infrared analysis. A notable change in grease microstructure was observed by AFM and SEM. The thickener morphology changed from an entangled helical fibril structure to particle-like nanofragments. The variation in thickener microstructure was observed in the early life grease, which suggested grease can experience an inconsistent aging process in the real-life bearings. Overall, 70.5 ± 1.37 wt% base oil bled from the fresh grease, 68.2 ± 0.73 wt% from the early life grease, 58.1 ± 2.33 wt% from the medium used grease, and 60.0 ± 6.35 wt% from the heavily used grease. The results suggest that the densely packed microstructure observed in the aged grease affects the capability of base oil bleeding from the grease. The retardation of base oil flow due to degraded grease may result in the lubricating ability of grease becoming compromised and hence result in an increased wear rate of the bearings.